Social Media a Concern for Foreign Relationships with Neighbor Countries - Hossan, Md. Alomgir (International Journal of Applied Research and Sustainable Sciences, 2023)
Indian Sub-continent, especially Bangladesh, India, and Pakistan were divided by Islamic ideology. Bangladesh gained independence from West Pakistan in 1971 with the unbelievable support of the neighboring country India. The present article attempts to find out about the recent time controversy through social media between these countries. In the 2023 Men’s World Cup Cricket Final match India vs Australia held on November 19, 2023, Australia won by 6 Wickets. Here Bangladeshi young cricket lovers enjoyed supporting Team Australia but Indians could not take it positively. They think Bangladesh as a Muslim country avoids Hindus and does not respect and love them. However, the study reveals that 83% disagree that Islam is related to support. 59.50% voted that a player’s behavior is responsible for the support of India and only 3% think that religion may affect supporting the cricket matches. Finally, an effective recommendation has been structured for resolving the crisis.